Post-procedural and long-term functional outcomes of jailed side branches in stented coronary bifurcation lesions assessed with side branch Murray law–based quantitative flow ratio - Xu, Ke; Jiang, Yue; Yang, Wentao; Zhang, Weifeng; Wang, Dong; Zhao, Yu; Zheng, Shunwen; Hao, Ziyong; Shen, Lan; Jiang, Lisheng; Qiu, Xingbiao; Escaned, Javier; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction In coronary bifurcation lesions treated with percutaneous coronary intervention (PCI) using a 1-stent strategy, the occurrence of side branch (SB) compromise may lead to long-term myocardial ischemia in the SB territory. Murray law–based quantitative flow ratio (μQFR) is a novel angiography-based approach estimating fractional flow reserve from a single angiographic view, and thus is more feasible to assess SB compromise in routine practice. However, its association with long-term SB coronary blood flow remains unknown. Methods A total of 146 patients with 313 non-left main bifurcation lesions receiving 1-stent strategy with drug-eluting stents was included in this retrospective study. These lesions had post-procedural Thrombolysis in Myocardial Infarction (TIMI) flow grade 3 in SBs, and documented angiographic images of index procedure and 6- to 24-month angiographic follow-up. Post-procedural SB μQFR was calculated. Long-term SB coronary blood flow was quantified with the TIMI grading system using angiograms acquired at angiographic follow-up. Results At follow-up, 8 (2.6%), 16 (5.1%), 61 (19.5%), and 228 (72.8%) SBs had a TIMI flow grade of 0, 1, 2, and 3, respectively. The incidences of long-term SB TIMI flow grade ≤1 and ≤2 both tended to decrease across the tertiles of post-procedural SB μQFR. The receiver operating characteristic curve analyses indicated the post-procedural SB μQFR ≤0.77 was the optimal cut-off value to identify long-term SB TIMI flow grade ≤1 (specificity, 37.50%; sensitivity, 87.20%; area under the curve, 0.6673; P = 0.0064), and it was independently associated with 2.57-fold increased risk (adjusted OR, 2.57; 95% CI, 1.02–7.25; P = 0.045) in long-term SB TIMI flow grade ≤1 after adjustment. Discussion Post-procedural SB μQFR was independently associated with increased risk in impaired SB TIMI flow at long-term follow-up. Further investigations should focus on whether PCI optimization based on μQFR may contribute to improve SB flow in the long term.